Deriving comprehensive structural information on long-chain branched polyethylenes from analysis of thermo-rheological complexity. (8th November 2016) - Stadler, Florian J.; Chun, Yong Sung; Han, Jae Hyuck; Lee, Eunwoong; Park, Seung Ho; Yang, Chun Byung; Choi, Changhyun
Abstract: An advanced analytic method, based mainly on thermorheological analysis of standard frequency sweeps at several temperatures, is introduced which can determine a host of rheological indicators for long-chain branched polyethylenes and other materials with an Arrhenius-type temperature dependence. The method can be used to classify and categorize unknown samples to material types (tubular and autoclave low density polyethylene, long-chain branched metallocene polyethylene). For long-chain branched metallocene polyethylenes, it is, furthermore, possible to determine molar mass and branching degree using established relations with rheological behavior. It is, therefore, possible to gain a rather comprehensive picture of the molecular structure of long-chain branched polyethylenes using only a relatively simple set of rheological experiments. An automated analysis routine facilitates the evaluation. Graphical abstract: Highlights: Thermorheological branching analysis from linear-viscoelastic data. Fully automatic analysis routine. Finds characteristic points and further analyzes them. Classification and comparison according to topography.